PERAN PENDAPATAN, MARKETPLACE DAN PEMBAYARAN DIGITAL TERHADAP PERILAKU DOOM SPENDING PADA KONSUMEN GENERASI Z - Devi Risky Wijayanti; Arfida Boedirochminarni (Program Studi Ekonomi Pembangunan, 2026)
This study aims to analyze doom spending behavior among Generation Z in Malang City within the context of consumption convenience in the digital era through marketplaces and digital payments. The research was conducted on Generation Z employees of Bank Jatim in Malang City during the period from May to July, using an online questionnaire distributed via Google Form as the data collection technique. The data were measured using a Likert scale and analyzed using the Partial Least Squares method. The results indicate that the marketplace variable has a significant effect on doom spending behavior, with an influence value of 48.6%. In contrast, income and digital payment variables do not have a significant effect, with coefficient values of -30.9% and -20%, respectively. These findings suggest that increased marketplace usage can encourage doom spending behavior among Generation Z, while higher income levels and increased use of digital payments do not necessarily lead to such behavior. This condition indicates that good financial literacy plays an important role in controlling doom spending behavior among Generation Z employees of Bank Jatim in Malang City.